A evolução da teoria contratual e sua repercussão na sociedade contemporânea: uma reflexão sobre a (des)credibilidade do contrato de consumo - Crespo, Danilo Leme (2018)
From the simple conventions and pacts foreseen in the Roman Empire to the creation of a formal contractual instrument; from the "Pacta Sunt Servanda" to the Contractual Direction; of the French Napoleon Code, which guaranteed liberty and volitional autonomy, to the Brazilian Code of Defense of the Consumer and Civil Code, with a singular restriction; these are small examples of the changes that the contract figure has suffered over the years, from a formal or material point of view, which is why law, doctrine and jurisprudence seek to adapt to this new reality. The old paradigms are no longer enough to solve the daily problems, mainly in the mass consumption brought by the Industrial Revolution and the Consumer Society. This traditional rule, which is an isolated analysis of a contract, gave rise to a new contracting technique, which was mainly carried out by the edition of the Consumer Protection Code (1990) and the new Civil Code (2002), which are intertwined because of dialogue. If, before, the legislation was based on individualism, the result of a Liberal State in which private autonomy and immutability had absolute contours, the Brazilian system changed drastically, adopting a position much more directed to the balance of the relation, to good faith the social function of the contract and, above all, the protection of consumer vulnerability, all converging to the constitutional principle of the dignity of the human person. The consumption contracts in Brazil, the target of the present work, have largely been standardized, of mere adherence and sometimes totally unbalanced, hence the reason - perhaps the greatest one - of state interventionism over classical liberalism. All this, together with the depersonalization of contractual relations in supposed benefit of the common good, brought a new legal panorama to these consumer contracts, with possible reflection on their social credibility. In fact, the analysis of such developments, notably its causes, characteristics and consequences, makes up the central object of the study proposed here. It is well seen that the theme is current, complex and inviting repercussion